Behaviour change strategies for internet, pornography and gaming addiction: A taxonomy and content analysis of professional and consumer websites. (July 2018) - Rodda, Simone N.; Booth, Natalia; Vacaru, Michael; Knaebe, Brenna; Hodgins, David C.
Abstract: There is a growing body of literature on internet-related behaviours and their associated problems, including Internet Addiction (IA). Although evidence suggests most people self-treat, little is known about the type, or efficacy, of the methods they implement. The current study sought to identify and describe the change strategies used to limit or reduce IA (including internet gaming and internet pornography). The study explored the content of 79 websites containing behaviour change advice provided by experts and consumers. A total of 4459 change strategies were identified. Through pragmatic content analysis, they were classified into 19 categories and organised into four phases of goal achievement. Across the entire sample, the most frequently promoted or discussed change strategy was seeking alternatives to internet usage (20% of total strategies), followed by maintaining readiness to change (10%), and avoidance of triggers of internet usage (10%). We found the frequency and content of 16 out of the 19 change strategies differs according to the type of internet problem (i.e., general, gaming, or pornography). This research provides detailed information for the development of tailored interventions. It indicates that interventions for IA could contain the same types of change strategies, but that the specific detail of strategies needs to be tailored towards the specific type of internet problem. Highlights: A broad range of behaviour change strategies for internet use are promoted online. Strategies for internet use are most frequently focused on limiting behaviour. Planning and evaluation are infrequently used strategies for limiting internet use. Intervention content should be specific for internet, gaming and pornography.